Exome Sequencing Identified a Splice Site Mutation in FHL1 that Causes Uruguay Syndrome, an X-Linked Disorder With Skeletal Muscle Hypertrophy and Premature Cardiac Death. (April 2016) - Xue, Yuan; Schoser, Benedikt; Rao, Aliz R.; Quadrelli, Roberto; Vaglio, Alicia; Rupp, Verena; Beichler, Christine; Nelson, Stanley F.; Schapacher-Tilp, Gudrun; Windpassinger, Christian; Wilcox, William R.
Abstract : Background—: Previously, we reported a rare X-linked disorder, Uruguay syndrome in a single family. The main features are pugilistic facies, skeletal deformities, and muscular hypertrophy despite a lack of exercise and cardiac ventricular hypertrophy leading to premature death. Methods and Results—: An ≈19 Mb critical region on X chromosome was identified through identity-by-descent analysis of 3 affected males. Exome sequencing was conducted on one affected male to identify the disease-causing gene and variant. A splice site variant (c.502-2A>G) in the FHL1 gene was highly suspicious among other candidate genes and variants. FHL1A is the predominant isoform of FHL1 in cardiac and skeletal muscle. Sequencing cDNA showed the splice site variant led to skipping of exons 6 of the FHL1A isoform, equivalent to the FHL1C isoform. Targeted analysis showed that this splice site variant cosegregated with disease in the family. Western blot and immunohistochemical analysis of muscle from the proband showed a significant decrease in protein expression of FHL1A. Real-time polymerase chain reaction analysis of different isoforms of FHL1 demonstrated that the FHL1C is markedly increased. Conclusions—: Mutations in the FHL1 gene have been reported in disorders with skeletal and cardiac myopathy but none has the skeletal or facial phenotype seen in patients with Uruguay syndrome. Our data suggest that a novel FHL1 splice site variant results in the absence of FHL1A and the abundance of FHL1C, which may contribute to the complex and severe phenotype. Mutation screening of the FHL1 gene should be considered for patients with uncharacterized myopathies and cardiomyopathies. Abstract : Supplemental Digital Content is available in the text.